THE INFLUENCE OF PERCEIVED E-SERVICE QUALITY DIMENSIONS ON CUSTOMER INTENTION TO REPURCHASE: A CASE OF MILLENNIAL GENERATION ON SHOPPING ONLINE IN INDONESIA - Sianturi, Charles M.; Pasaribu, Johnson; Rajagukguk, Jonson; Sianturi, Cyndia Audria (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
The purpose of this article is to investigate the relationship between e-service quality dimensions and repurchase intention of millennial generation of Indonesia on online shopping behavior. A qualitative review of e-service quality dimension and intention to repurchase construct was conducted to identify the relationship between the constructs. This study focuses on seven e-service quality dimensions to predict repurchase intention. The results are expected to extend the knowledge of different context of e-service quality measurement and its consequences. A survey was conducted to 100 judgement sample size of shopping online consumers by distributing self administered questionnaires. To test the proposed model is by using multi regression was employee. The analytical results showed that all of perceived e-service quality dimensions namely ; privacy, system availability, contact, compensation, responsiveness, fulfillment, and efficiency affected intention to repurchase differently based on the value of regression coefficients and all dimensions statistically significant. Future research should consider a variety of e-service and segment and using different methodology such as in-depth interview or longitudinal study.